Analisis Tingkat Literasi Keuangan UMKM di Kawasan Lapangan Saparua, Kota Bandung - Wildan Gilang Komara; Dr. Ratna Meisa Da'i; Dr. Suryanto (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
Currently, MSMEs are one of the sectors that play a major role in the Indonesian economy. However, in establishing MSMEs, good financial literacy knowledge is needed, because this knowledge can provide an understanding of the basic concepts of financial products, good financial planning and management, as well as protection from financial crime in the form of fraud or fraudulent investments. This study aims to determine what kind of understanding and level of financial literacy owned by MSME players in the Saparua Field area, Bandung City. The research is a descriptive research with quantitative research methods. The data analysis method uses descriptive analysis and multiple linear regression analysis. According to the result of the research, it was found that the financial literacy level of Saparua Field MSMEs was at a fairly high and very high level. It was also found that age has a significant influence on the level of financial literacy. The conclusion obtained is that MSMEs in Saparua Field have been well literate in terms of financial literacy.